Light scattering from a diffractive-refractive intraocular lens: a goniometer-based approach for individual zone assessment - Łabuz, Grzegorz; Berg, Thomas J. T. P. van den; Auffarth, Gerd U.; Khoramnia, Ramin (Biomedical optics express, 2022)
We proposed and tested a method to measure light scattering from the diffractive lens profile in an echelle element featuring 9 zones. Measurements were performed using a goniometer-based setup up to 7.5°. The proportion of scattered light was calculated to derive the loss of light. Material scattering was minimal (∼1 deg2/sr); however, each echelle zone acted as a scattering source. A nearly gradual straylight increase was found with the zone number showing peak intensity between 3° and 3.75°. An estimated 6.2% ± 0.1% was lost due to scattering, which ought to be considered when reporting an IOL’s light loss.
Gesehen am 15.11.2023